2017 ASEE Annual Conference &Amp; Exposition Proceedings
DOI: 10.18260/1-2--28113
|View full text |Cite
|
Sign up to set email alerts
|

Design and Implementation of an Aspirational Ethics Laboratory Course

Abstract: I am a teacher educator with a special interest in teacher induction and retention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…This questionnaire covered questions ranging from how much control they had on the overall lab itself, to how confident they felt in their competency in the material itself. Many of the questions were consistent with prior survey questions tied to understanding the larger curriculum modification as outlined in prior papers [1][2][3].…”
Section: Student Survey Assessmentmentioning
confidence: 79%
See 2 more Smart Citations
“…This questionnaire covered questions ranging from how much control they had on the overall lab itself, to how confident they felt in their competency in the material itself. Many of the questions were consistent with prior survey questions tied to understanding the larger curriculum modification as outlined in prior papers [1][2][3].…”
Section: Student Survey Assessmentmentioning
confidence: 79%
“…The overall goal of the project is to improve how engineering students learn particular concepts which are pertinent throughout the four-year mechanical engineering curriculum [1]- [3]. It is possible to assess the success of these new laboratory modules through using evidence collected via surveys conducted after the lab the module was completed by students.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Without a strong understanding of concepts, engineers may create flawed designs that do not function as intended. Efforts to include more hands-on, conceptual activities have been made in mechanical engineering 3,4,5 , civil engineering 6,7,8,9 , and environmental engineering 10,11 . Brown et al (2014) developed an open channel desktop module, and found that student conceptual understanding increased when using the module.…”
Section: Introductionmentioning
confidence: 99%
“…When there is only one piece of lab equipment, students often become disengaged. Studies in mechanical engineering have demonstrated that laboratory experiments conducted with smaller, less expensive equipment in small groups greatly increased student engagement 3,4,5 . Smaller, less expensive desktop modules may help improve student engagement and provide students with more hands-on experience.…”
Section: Introductionmentioning
confidence: 99%